Controlling perpetrators of spreading fake news in the Southern Sumatra regional police - Victor Fitrizal Auli; Kiagus Muhammad Sobri; Sriati; Sena Putra Prabujaya (Faculty of Communications Science, Dr. Soetomo University, 2024)
The continuous development of information technology brings significant changes in various fields of community life. Society and the internet have a very complex and significant relationship, especially in terms of using the internet as a means of socialisation and interaction. In the context of social media abuse, people are often trapped in complex issues that lead to hoaxes and hate speech. This study examines policies, control measures, and punishment for hoax spreaders in the South Sumatra Regional Police jurisdiction. This research employs qualitative research using empirical studies and a legal, sociological framework. This research aims to contribute to the corpus of literature and information regarding the perpetrators of spreading false news (hoax) at the South Sumatra Regional Police. The findings of this study reveal that criminal law enforcement against fake news spreaders (hoaxes) in the South Sumatra Regional Police have procedures or efforts to resolve cases of fake news (hoax); the procedure includes receiving reports/complaints, investigations, investigations, sending SPDP (Notice of Commencement of Investigation), sending case files, and transferring suspects and evidence. Law enforcement entities involved in combating fake news are the Police, Prosecutors, and Judges. This research provides the latest data in 2022 regarding cases of spreading fake news (Hoax) in the South Sumatra Regional Police.